Leber's hereditary optic neuropathy: mitochondrial and biochemical studies on muscle biopsies. Issue 7 (July 1987) - Uemura, A; Osame, M; Nakagawa, M; Nakahara, K; Sameshima, M; Ohba, N
Abstract : Two patients with Leber's hereditary optic neuropathy underwent morphological and biochemical investigations of muscle biopsy samples from the biceps brachii. Although clinically there was no muscle weakness or atrophy, specific histochemical and electron microscopic examinations showed mild but distinct myopathic changes, including abnormal oxidative enzyme activities, aggregates of enlarged mitochondria in the subsarcolemmal regions, and disruptions of myofilaments. Biochemical analyses of mitochondria isolated from muscle samples did not show and deficiency in respiratory-chain enzyme complexes or defect in content of cytochromes. Leber's hereditary optic neuropathy is assumed to be a multisystem disorder involving skeletal muscle also.